ICGG 2018 - proceedings of the 18th International Conference on Geometry and Graphics : 40th anniversary - Milan, Italy, August 3-7, 2018 /: 40th anniversary - Milan, Italy, August 3-7, 2018. ([2019]) - Unknown
No abstract available